2022
DOI: 10.3390/v14050889
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Phylodynamic Analysis Reveals the Dispersal Patterns of African Swine Fever Virus

Abstract: The evolutionary and demographic history of African swine fever virus (ASFV) is potentially quite valuable for developing efficient and sustainable management strategies. In this study, we performed phylogenetic, phylodynamic, and phylogeographic analyses of worldwide ASFV based on complete ASFV genomes, B646L gene, and E183L gene sequences obtained from NCBI to understand the epidemiology of ASFV. Bayesian phylodynamic analysis and phylogenetic analysis showed highly similar results of group clustering betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Te genome-wide genome similarity between ASFV genotype I and genotype II ranges between 82.4-94.7%. A few molecular epidemiology studies based on genome sequences have been conducted to reconstruct the evolution of ASFV globally or to trace the origin and evolution of genotype I ASFV in Sardinia [24][25][26]. Up to date, the evolutionary dynamics of genotype II ASFV, currently widespread in Eurasia remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Te genome-wide genome similarity between ASFV genotype I and genotype II ranges between 82.4-94.7%. A few molecular epidemiology studies based on genome sequences have been conducted to reconstruct the evolution of ASFV globally or to trace the origin and evolution of genotype I ASFV in Sardinia [24][25][26]. Up to date, the evolutionary dynamics of genotype II ASFV, currently widespread in Eurasia remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of ASFV genome variation have been identified including the gain or loss of MGF members, deletion or insertion of genomic fragments, variation in the numbers of repeat units in the tandem repeat sequences, polymer tract variation and single nucleotide variation. Molecular epidemiology studies based on genome sequences have been conducted to reconstruct the evolution of ASFV globally or trace the origin and evolution of genotype I ASFV in Sardinia [ 21 , 22 , 23 , 24 ]. Genomic epidemiology analysis has demonstrated that genotype II ASFV in Eurasia has evolved into genetic clusters defined by eight anchor mutations [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other dsDNA viruses, ASFV genome is highly conserved, and nucleotide substitution the main driving force of genomic evolution occurs at extremely slow rate ( Shen et al. 2022 ).…”
Section: Introductionmentioning
confidence: 99%